Long-run performance of sovereign rating changes - Correia, Claúdia (2007)
This paper examines the impact of Sovereign rating changes on the aggregate stock and bond market returns both in emerging and developed countries. Rating downgrades in emerging markets are associated with significant negative wealth effects both in the stock and bond markets. Moreover, the effects of rating downgrades persist up to six-months after the event. In contrast, upgrades in emerging markets convey no information. Rating changes in developed markets have no significant impact on either stock and bond market returns. Rating agencies act pro-cyclically, downgrading countries in bad times and, consequently, contributing to the instability in emerging markets.